2019
DOI: 10.59077/jwfx6154
|View full text |Cite
|
Sign up to set email alerts
|

Dark Parenting: Parents Who Score as High in the Dark Triad Demonstrate Sub-Optimal Parenting Styles

Abstract: The Dark Triad of personality, including the traits of Machiavellianism, psychopathy, and narcissism, have been shown to strongly predict a broad array of social and behavioral outcomes-particularly in the domain of mating. From an evolutionary perspective, the parenting domain of life is just as critical as is the mating domain: Parenting behaviors bear directly on long-term reproductive success. In spite of this fact, little past research has examined the relationship between the Dark Triad and parenting beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…One might have expected some of the Dark Triad traits to have served as significant predictors of people's strength of attachment to their pets, particularly considering the correlation (albeit modest) that was unearthed between Machiavellianism and LAPS scores. The Dark Triad has been associated with various indicators of parenting style, with authoritative parenting being negatively correlated with Dark Triad tendencies and authoritarian and detached parenting more positively correlated with these traits (69). Vonk and colleagues (70) also found that people who were high in grandiose narcissism [as assessed by the 'Pathological Narcissism Inventory, (71)] were more attached to their 'traditional' pets (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One might have expected some of the Dark Triad traits to have served as significant predictors of people's strength of attachment to their pets, particularly considering the correlation (albeit modest) that was unearthed between Machiavellianism and LAPS scores. The Dark Triad has been associated with various indicators of parenting style, with authoritative parenting being negatively correlated with Dark Triad tendencies and authoritarian and detached parenting more positively correlated with these traits (69). Vonk and colleagues (70) also found that people who were high in grandiose narcissism [as assessed by the 'Pathological Narcissism Inventory, (71)] were more attached to their 'traditional' pets (e.g.…”
Section: Discussionmentioning
confidence: 99%